The Influence of School’s Culture on Multicultural Education in Indonesia - Yuliana, Yuliana; Riswanto, Riswanto (Journal of Social Work and Science Education, 2025)
This study investigates the role of school’s culture in supporting the implementation of multicultural education in Indonesia through a systematic literature review. Using PRISMA guidelines and Braun and Clarke’s thematic analysis model, the study synthesized findings from selected national and international literature. The results show that school’s culture plays a critical role in shaping inclusive school environments, strengthening tolerance, and supporting character development aligned with multicultural values. Two dominant themes emerged: (1) leadership and institutional capacity, and (2) cultural responsiveness in pedagogy and curriculum. However, several challenges were identified, including the lack of a unified definition of school’s culture, limited empirical studies on its practical application, and variations in implementation across different local contexts. This research concludes that school’s culture can serve as valuable social capital in advancing multicultural education, but its effectiveness requires strategic support through policy, teacher training, and contextual adaptation. These findings provide theoretical and practical contributions to strengthening inclusive education in Indonesia.